Systematic Review of Virtual Worlds applied in Education - Nunes, Felipe Becker; Herpich, Fabrício; Paschoal, Leo Natan; Tarouco, Liane Margarida Rockenbach; de Lima, José Valdeni (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2016)
Growth of research conducted over the past year involving the application of virtual worlds in the educational field enabled the development of didactic interventions, which aim to complement the learning process of students. Based on this assumption, this paper presents an analysis based on a systematic review of virtual worlds applied in the educational context seeking to highlight qualitative and quantitative information found during the application of a previously established protocol. Analysis of data provided enlightening information about certain listed aspects, taking as an example the allocated type of target audience, the areas of education and theories that have grounded the research conducted.